Association of remnant cholesterol with CVD incidence: a general population cohort study in Southwest China - Liu, Chengxi; Dai, Mi; Tian, Kunming; Zhou, Shiyu; Luo, Lei; Zeng, Zhiying; Yan, Xuelian; Xiao, Ying; Wang, Yiying; Deng, Renli; Lei, Xiuhong; Liu, Tao (Frontiers in Cardiovascular Medicine, 2023)
Background Emerging evidence has indicated that remnant cholesterol (RC) could predict cardiovascular disease (CVD) incidence. Nevertheless, the relationship between RC and CVD risk, especially within the general Chinese population, remains scarce. Objective The present research aimed to assess whether RC concentrations and CVD outcomes in general Chinese adults are related. Methods The Cox proportional hazard model was established to explore the relationship between RC and the outcomes of CVD and CVD subgroups. A restricted cubic spline (RCS) was utilized to investigate the dose–response connection between RC and the risk of CVD outcomes, and the ROC curve was used to calculate the corresponding cutoff values. Moreover, stratified analysis was conducted to investigate the potential effect modification in the association between RC and CVD outcomes. Results Significant positive associations were found between elevated categorical RC and increased risk of CVD (HR Q4, 1.80; 95% CI 1.15–2.79; P-value = 0.008), atherosclerotic cardiovascular disease (HR Q4, 2.00; 95% CI 1.22–3.27; P-value = 0.007), stroke (HR Q4, 1.66; 95% CI 1.02–2.69; P-value = 0.040), and ischemic stroke (HR Q4, 1.87, 95% CI 1.08–3.25; P-value = 0.034), respectively. Our study suggested that the incidence of CVD outcomes increased when RC levels were above 0.75 mmol/L. Importantly, the CVD risks related to RC were more likely to be those found in subjects aged above 60 years, women, subjects with BMI <24 kg/m2, and subjects with hypertension and unhealthy diet patterns. Conclusions Aberrant high level of RC is associated with elevated CVD risk, independent of low-density lipoprotein cholesterol (LDL-C). Our data reveal urgent primary prevention for subjects with high RC levels to a low incidence of CVD, especially for the elderly, women, and those with hypertension and unhealthy diet patterns.